IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN BAHASA INGGRIS DI TINGKAT SMP - Aisya Agustina; Hepy Adityarini (JURNAL KONFIKS, 2025)
This study aims to analyze teachers’ perceptions, implementation strategies, and challenges in applying the Deep Learning approach in English language teaching at the junior high school level. Using a qualitative descriptive design, data were collected through semi structured interviews with six English teachers who are members of the Muhammadiyah MGMP in Surakarta. The study focuses on how teachers understand the concept of Deep Learning, how they translate this understanding into daily instructional practices, and how they respond to the obstacles that arise during implementation. The findings indicate that teachers perceive Deep Learning as a meaningful, mindful, and joyful learning process that encourages students to think critically, build conceptual connections, and relate learning materials to real life experiences. In practice, teachers employ various strategies such as contextual tasks, collaborative discussions, problem solving activities, simple project work, and engaging learning activities designed to promote student motivation and participation. However, teachers also encounter several challenges, including limited instructional time, inflexible classroom conditions, and difficulties in designing activities that accommodate students’ diverse needs and proficiency levels. To address these issues, teachers develop more structured lesson plans, adjust activities based on classroom realities, and utilize the MGMP forum as a collaborative space to share experiences and refine instructional strategies. These findings emphasize the importance of teacher training programs that focus on designing adaptable and practical Deep Learning based instructional activities suitable for diverse school contexts.